MISCONCEPTION AND BLINDNESS: A PERSPECTIVE OF PAKISTANI COMMUNITY (Contemporary Journal of Social Science Review, 2025)
The study explored misconceptions about blindness within the Pakistani community. Using a descriptive survey design, data were collected from 51 urban residents through simple random sampling. Participants, primarily educated individuals, responded to a structured questionnaire with 20 close-ended statements addressing positive and negative stereotypes about blindness. Data collection occurred in-person at educational institutions, local places, and markets, as well as via smartphone, email, and WhatsApp. Quantitative analysis methods included mean, standard deviation, independent t-tests, and analysis of variance. Findings revealed that positive misconceptions about blind individuals included perceptions of sharp intellectual abilities, enhanced judgment skills, and strong concentration capabilities. Negative stereotypes portrayed blind individuals as objects of pity, unsafe navigating spaces independently, and assumed them to share similar interests. No significant gender-based differences (p=0.397) were found, indicating similar perceptions across males and females. There was a statistically significant difference (p=0.12) in misconceptions about blindness among different age groups. The results suggested that misconceptions about blindness differ significantly between certain age groups, especially between the middle-aged (36-45 years) and younger (16-35 years) groups. No significant difference (p=0.459) was found in misconceptions based on the qualification. The common people had higher level of positive stereotypical behaviors in comparison to their negative misconceptions.